Current-Driven Vortex Domain Wall Motion in Wire-Tube Nanostructures - Escrig-Murua, J; Espejo-Pina, A; Vidal-Silva, N (American Institute of Physics, 2015)
We have investigated the current-driven domain wall motion in nanostructures comprised of a pair of nanotube and nanowire segments. Under certain values of external magnetic fields, it is possible to pin a vortex domain wall in the transition zone between the wire and tube segments. We explored the behavior of this domain wall under the action of an electron flow applied in the opposite direction to the magnetic field. Thus, for a fixed magnetic field, it is possible to release a domain wall pinned simply by increasing the intensity of the current density, or conversely, for a fixed current density, it is possible to release the domain wall simply decreasing the magnetic external field. When the domain wall remains pinned due to the competition between the current density and the magnetic external field, it exhibits a oscillation frequency close to 8 GHz. The amplitude of the oscillations increases with the current density and decreases over time. On the other hand, when the domain wall is released and propagated through the tube segment, this shows the standard separation between a steady and a precessional regime. The ability to pin and release a domain wall by varying the geometric parameters, the current density, or the magnetic field transforms these wire-tube nanostructures in an interesting alternative as an on/off switch nano-transistor. © 2015 AIP Publishing LLC.